Agrobacterium-mediated transformation of oil palm (Elaeis guineensis jacq.) suspension culture - Roowi, Siti Habsah (2003)
The life cycle of flowering plants in general can be divided into two growth phases: vegetative and reproductive. The reproductive phase can be subdivided into the development of the inflorescence meristem and floral meristems. Control of flowering and the regulation of plant architecture has been thoroughly investigated in a number of wellstudied dicot plants such as Arabidopsis, Antirrhinum, tomato and tobacco. However, in monocot plants, molecular information related to plant reproduction is still limited. In A rabidopsis , the Terminal Flowering I(TFLI) gene, LEAFY, and the target genes of CONSTANS (CO) including the FLOWERING LOCUS T (FI) and SUPPRESSOR OF OVEREXPRESSION OF COI (SOCI) genes, have a major role in promoting flowering and thus controlling flowering time. To investigate the regulation of meristem identity as well as the control of floral transition in oil palm, we transferred genes pCAMBIA/TFL1, pCAMBIA/JIT60, pCAMBIA/LFY, pGA/LFY and pCAMBIA/SOCl into oil palm embryogenic callus. This present study focuses on the optimization of Agrobacterium-mediated transformation and the analysis of transgenic plants. The objective of this study was also to clone the putative oil palm (OPSOCI and OPLFy) genes into a plasmid binary vector system, so as to transform these genes into oil palm embryogenic callus and to determine their effect on expression driven by a cauliflower mosaic virus (CaMV) 35S promoter in oil palm. The success of gene delivery using Agrobacterium into the plant genome is often based on several factors including temperature used during co-cultivation, the binary vector and promoters used, and the plant genotype itself. The most important factors contributing to the success of T -DNA transfer is the type of plant material used. We used embryogenic suspension cells as starting material for the transformation of oil palm because of the large numbers of totipotent cells found in these cultures.